2011
DOI: 10.4236/psych.2011.27110
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Impulsivity and Technical Performance in Handball Female Athletes

Abstract: A complex and dynamic environment where impulsivity probably interferes in the human behavior is the sport context. The aim of this exploratory study was to investigate the possible relationship between impulsivity and technical performance in handball athletes. Eleven junior female athletes on a handball team were submitted to a neuropsychological assessment of impulsivity using Conner's CPT-II and the Iowa Gambling Task. In 11 matches, participants' handball performance was analyzed. We adopted the resamplin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 17 publications
0
24
1
5
Order By: Relevance
“…Dickman 2 proposes the existence of functional impulsivity, which refers to the tendency to act with relatively little forethought when the subject needs to make fast decisions. For example, according to Lage et al, 3 some types of impulsive behaviors are related to better performance in certain contexts (e.g., sports practice). Even in clinical samples, functional impulsivity seems to be related to better functioning of attention, reaction time, and goal-directed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Dickman 2 proposes the existence of functional impulsivity, which refers to the tendency to act with relatively little forethought when the subject needs to make fast decisions. For example, according to Lage et al, 3 some types of impulsive behaviors are related to better performance in certain contexts (e.g., sports practice). Even in clinical samples, functional impulsivity seems to be related to better functioning of attention, reaction time, and goal-directed behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Logan, Schachar, and Tannock (1997) further reported problems with inhibitory control in more impulsive participants as was evident in their study from significantly longer stop-signal reaction times. More recently Lage et al (2011) reported that in handball female athletes' impulsivity as measured by Conner's Continuous Performance Task (CPT-II) and the Iowa Gambling Task (IGT) was positively correlated with offensive fouls. The researchers suggested that this type of non-planning impulsivity results in risky decisions that may seem to produce immediate rewards but are potentially fraught with longer-term negative consequences (e.g.…”
Section: Discussionmentioning
confidence: 98%
“…O construto de investigação da influência da impulsividade sobre os comportamentos táticos de jogadores de futebol das categorias de base pode ser fundamental para o surgimento de novas perspectivas no processo de identificação e treinamento de futuros talentos (Lage et al, 2011;Vestberg, Gustafson, Maurex, Ingvar, & Petrovic, 2012). Porém, para investigar como a impulsividade pode condicionar o comportamento tático dos jogadores, torna-se importante a utilização de protocolos de avaliação que permitam mensurar essas duas variáveis de maneira precisa.…”
Section: Relación Entre Impulsividad Y Comportamiento Táctico De Jugaunclassified
“…Para a avaliação da impulsividade, adotam-se com frequência testes computadorizados que simulam uma tarefa simples e de natureza cotidiana, mas que, ao mesmo tempo, exige do sujeito avaliado uma tomada de decisão a partir de alguns constrangimentos, como a possibilidade de ganhar ou perder algo (Lage et al, 2011;Malloy-Diniz et al, 2008). Entre esses testes, destaca-se o Iowa Gambling Task (IGT); esse instrumento neuropsicológico vem sendo um grande referencial na avaliação da tomada de decisão sob incerteza, fornecendo informações sobre o grau de impulsividade por não planejamento do indivíduo.…”
Section: Relación Entre Impulsividad Y Comportamiento Táctico De Jugaunclassified
See 1 more Smart Citation